Betteshanger Colliery strike, 1942 (1942)
1942 1939-1945 "Betteshanger Colliery strike, 1942" [HFR0212], 1942 On 9 January 1942 miners at Betteshanger Colliery near Deal in Kent struck for 19 days over the level of allowances for working difficult seams. This was in breach of the wartime emergency regulations on compulsory arbitration and the Ministry of Labour decided to prosecute 1,050 miners for contravening Order 1305. Three local union officials were imprisoned and over a thousand strikers were fined. Other pits came out in sympathy and on 28 January a settlement was reached. In February, the Home Secretary dropped the prison sentences and most fines were never paid.